Quantifying a successful translation: A cognitive frame analysis of (un)translatability - Ingie Zakaria (LingBaW)
Assessing the success of a translated text is one of the controversial topics often discussed in the field of translation studies. The definition of a so-called successful translation is itself controversial. Therefore, for the purpose of this study, the success of a given translation may be defined as transmitting a similar, though rarely identical, semantic frame reference in the Target Language (TL) as was intended by the Source Language (SL) and may be quantified by comparing alternate translations and choosing the one with the highest number of equivalent frame references. One of the factors which could be considered detrimental to the production of a successful translation, as defined above, is the (un)translatability of cultural terms. Cultural terms, defined here as expressions referring to concepts or entities that are unique to a certain culture, are believed to be untranslatable. This paper uses Arabic visual frames referencing the Egyptian garment ǧal-labiy-ya (or ǧilbāb) as an example and argues that (un)translatability can be quantified using semantic frames based on the assumption that all SL terms have multiple frame references, some of which, mostly the ones indicating denotative meaning, have parallels in the TL while some others, mostly the ones indicating connotative meaning, do not. The degree of (un)translatability may, therefore, be quantifiable by observing which TL terms possess a higher rate of similar frame references in SL, which aids in the evaluation of translated texts in terms of relative equivalence and the degree to which the Target Text (TT) audience receives similar information to that received by the Source Text (ST) audience.